How to control selectivity in alkane oxidation?. Issue 8 (11th January 2019) - Li, Xuan; Teschner, Detre; Streibel, Verena; Lunkenbein, Thomas; Masliuk, Liudmyla; Fu, Teng; Wang, Yuanqing; Jones, Travis; Seitz, Friedrich; Girgsdies, Frank; Rosowski, Frank; Schlögl, Robert; et al.
Abstract : The bulk crystal structure of an oxidation catalyst as the most popular descriptor in oxidation catalysis is not solely responsible for catalytic performance. Abstract : The well-defined particle morphology of crystalline MnWO4 catalysts investigated in the present study facilitates obtaining insight into the origin of selectivity limitations in alkane oxidation. Hydrothermal synthesis at variable pH values granted access to a series of phase-pure MnWO4 catalysts with particles ranging from cube-like (aspect ratio 1.5) to rod- or needle-like (aspect ratio 6.8) shapes. Kinetic studies reveal a strong dependence of the propane consumption rate on the particle shape. The true origin of the structure sensitivity was unraveled by comprehensive bulk and surface analysis using nitrogen adsorption, XRD, SEM, ADF-STEM, STEM-EELS, XPS, multi-laser excitation Raman and DRIFT/operando FTIR spectroscopies, temperature-programmed oxidation (TPO), in situ NEXAFS, and DFT calculations. The active phase is composed of a thin manganese oxy-hydroxide layer formed on the surface of crystalline MnWO4. The differences in catalytic performance within the series clearly illustrate that the structural motif as the most popular descriptor in oxidation catalysis is not essential, since all MnWO4 catalysts in the series under study exhibit the same bulk crystal structure and bulk chemical composition and are phase pure and homogenous. The variable particle shape serves as a proxy that reflects the formation of varying abundance of redox active Mn 2+ /Mn 3+ surface sites, which correlates with catalytic activity. Operando FTIR spectroscopy directly confirms the formation of Mn–OH surface species by abstraction of hydrogen atoms from the propane molecule on nucleophilic oxygen atoms and suggests that active site regeneration occurs via oxidative dehydrogenation of Mn–OH species indicating a single-site nature of the active sites that does not allow four-electron reduction of molecular oxygen. Instead, intermediates are created that cause side reactions and lower the selectivity. The findings highlight fundamental design criteria that may be applied to advance the development of new alkane oxidation catalysts with improved selectivity.